Wegener's Granulomatosis with Extensive Bone Abnormalities Mimicking Fungal Sinusitis - Satoru Kodama; Nozomi Nomi; Masashi Suzuki (Case Reports in Otolaryngology)
Abnormalities of the underlying bone of the paranasal sinuses have sometimes been shown in Wegener’s granulomatosis (WG). We describe an interesting case of WG with extensive bone abnormalities in the sinuses mimicking fungal sinusitis. A 30-year-old woman presented with intermittent unilateral epistaxis. Biopsy was performed for the granulation tissue in the right nasal cavity, and she was diagnosed as having WG. Computed tomography (CT) revealed a ring-like calcification, mimicking a fungus ball, in the right maxillary sinus. Endoscopic sinus surgery was performed to confirm the diagnosis. A spherical bony structure, surrounded by granulation tissue, was identified in the maxillary sinus. The wall of the “bony ball” was fragile, like an egg shell. No fungus was found in the sinus. Thus, the extensive bone abnormalities were due to WG.